Pengembangan Gambar Berseri Berbasis Puzzle sebagai Media Pembelajaran Menulis Teks Narasi Sederhana Kelas 3 Sekolah Dasar - Syarifah Ifah; Dian Miranda; Bayu Prasodjo (ALSYS, 2026)
The ability to write simple narrative texts with coherent plot sequences among third-grade elementary school students remains low, thereby necessitating learning media that can help them construct narrative texts systematically. This study aimed to produce a Puzzle-Based Picture Series as a learning medium for writing simple narrative texts for third-grade elementary school students that is suitable for use. The research employed a Research and Development (R&D) method by adapting the ADDIE model and focusing on the Analysis, Design, and Development stages. The research subjects consisted of four validators (two questionnaire instrument validators and two product validators comprising a material expert and a media expert), one classroom teacher, and 29 students. Data were collected through interviews, questionnaires, and documentation, and were analyzed descriptively and quantitatively to assess the feasibility of the developed product. The results showed that the developed medium obtained an average feasibility score of 4.00 for the material aspect and 3.96 for the media aspect, both falling into the “Highly Feasible” category. These results were reinforced by the teacher response test with a score of 97.5% and student responses with a score of 90.16%, both categorized as “Very Good.” The study concludes that the Puzzle-Based Picture Series is suitable for use as a learning medium and has the potential to support the teaching of simple narrative text writing among third-grade elementary school students. Its implications indicate that this medium can be utilized by teachers as an alternative creative learning resource to enhance student engagement and narrative writing skills.